Armed Forces and Society in Europe - Forster, A. author. aut Link
VIII, 320 p.
Keywords: In the post-Cold War era, European militaries are engaged in an ongoing adaptation which is challenging relations between armed forces and the societies that they serve. This book offers an innovative conceptual framework to critically evaluate contemporary civil-military relations across the continent of Europe. It analyzes eight key issues in armed forces and society relations, to explore the scale and intensity of these changes.